(untitled) (Research, Society and Development, 2020)
The present study aimed to socialize the experiences of a research group in a human capital formation laboratory. It is an experience report of the proposal for the continuity of academic activities of a research group focused on the formation of human capital for the nursing area. The research group is part of the Academic Program in Health Care Sciences at Universidade Federal Fluminense, in Niterói (RJ). The activities carried out in the research group enabled several training strategies, culminating in the so-called “human capital formation laboratory”. The strategies constituted an important means of training and qualifying human capital, since the joint activities allowed to share knowledge in favor of the advances of the community.